Waist-to-hip ratio versus body mass index as predictors of fitness in women - Pawłowski, B; Dunbar, R (Springer, 2005)
The claim that men prefer women with low waist-to-hip ratios (WHR) has been vigorously disputed. We examine self-report data from 359 primiparous Polish women (with normal singleton births and healthy infants) and show that WHR correlates with at least one component of a women's biological fitness (her first child's birth weight, a variable that significantly affects infant survival rates). However, a woman's Body Mass Index (BMI) is a better predictor of her child's neonatal weight in small-bodied women (<54 kg). The failure to find a preference for low WHR in some traditional populations may thus be a consequence of the fact that, even in western populations, body mass is a better predictor of fitness in those cases characterized by low maternal body weight.